The Changes They are A-Timed: Metabolism, Endogenous Clocks, and the Timing of Puberty - Tolson, Kristen P.; Chappell, Patrick E. (Frontiers in Endocrinology, 2012)
Childhood obesity has increased dramatically over the last several decades, particularly in industrialized countries, often accompanied by acceleration of pubertal progression and associated reproductive abnormalities (Biro et al., 2006, Rosenfield et al., 2009). It has long been thought that the timing of pubertal initiation and progression in mammals is most likely dependent on nutritional and metabolic state, leading to the hypothesis that deviations from normal metabolic rate, such as those seen in obesity, may contribute to observed alterations in the rate of pubertal progression. This review will explore previous and current models of pubertal timing, outlining a potential role of endogenous timing mechanisms such as cellular circadian clocks in the initiation of puberty, and how these clocks might be altered by metabolic factors. Additionally, we will examine recently elucidated neuroendocrine regulators of pubertal progression such as kisspeptin, explore models detailing how the mammalian reproductive axis is silenced during the juvenile period and reactivated at appropriate developmental times, and emphasize how metabolic dysfunction such as childhood obesity may alter timing cues that advance or delay pubertal progression, resulting in diminished reproductive capacity.